2017
DOI: 10.1097/sla.0000000000001796
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Procedure-specific Risk Into the ACS-NSQIP Surgical Risk Calculator Improves the Prediction of Morbidity and Mortality After Pancreatoduodenectomy

Abstract: Procedure-specific complication risk influences outcomes after pancreatoduodenectomy; therefore, risk adjustment for performance assessment and comparative research should consider these preoperative and intraoperative factors along with conventional ACS-NSQIP preoperative variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 36 publications
6
48
0
3
Order By: Relevance
“…We analyzed a large cohort of patients from two consociated, high-volume centers sharing a standardized technique for PJ with an overall CR-POPF rate of 16.8%, which is consistent with rates reported by other high-volume Institutions. [25][26][27] The main finding of the present study confirms what we have previously reported, 23 that PE sutures are independently associated with a lower incidence of CR-POPF. This potential protective effect against CR-POPF is virtually maintained across all CR-POPF risk zones, but the negligible risk group, in which the POPF incidence is nil.…”
Section: Discussionsupporting
confidence: 92%
“…We analyzed a large cohort of patients from two consociated, high-volume centers sharing a standardized technique for PJ with an overall CR-POPF rate of 16.8%, which is consistent with rates reported by other high-volume Institutions. [25][26][27] The main finding of the present study confirms what we have previously reported, 23 that PE sutures are independently associated with a lower incidence of CR-POPF. This potential protective effect against CR-POPF is virtually maintained across all CR-POPF risk zones, but the negligible risk group, in which the POPF incidence is nil.…”
Section: Discussionsupporting
confidence: 92%
“…Several large-volume databases have also been utilized to develop preoperative and postoperative risk stratification protocols for a given procedure. The results from large database studies provide better evidence-based guidelines for decisions made regarding patient care preoperatively, intraoperatively, and postoperatively (10)(11)(12).…”
Section: Large-volume Databasesmentioning
confidence: 99%
“…This risk calculator was not procedure‐specific, but it performed well when tested in procedure‐specific populations . However, a recent study that included patients undergoing pancreatoduodenectomy showed that incorporating procedure‐specific complications improved the prediction of morbidity and mortality compared to the NSQIP universal surgical risk calculator . We did not develop procedure‐specific scores because of small sample size for some procedures.…”
Section: Discussionmentioning
confidence: 99%
“…36 However, a recent study that included patients undergoing pancreatoduodenectomy showed that incorporating procedure-specific complications improved the prediction of morbidity and mortality compared to the NSQIP universal surgical risk calculator. 36,37 We did not develop procedure-specific scores because of small sample size for some procedures. Moreover, it may not be practical to develop, maintain, update, and use separate comorbidity scores for each procedure and outcome.…”
Section: Discussionmentioning
confidence: 99%